Investment Performance of Equity Linked Savings Schemes - An Empirical Study - Chavali, Kavita; Jain, Shefali (Indian Journal of Finance, 2009)
Tax saving is the motive of any Indian investor today with increasing average income and cash inflows. Investors have a choice of investing in a lot of traditional tax saving instruments. They are all supported by Government of India and offer low rate of return with long lock-in periods. The study evaluates the performance of equity-linked saving schemes selected at random vis-Ã -vis the traditional schemes to give an insight into how these funds perform with respect to risk and returns. This is done to help investors to choose an ideal option to save tax and enjoy the benefits of investing in equity market which offers good returns.